Evaluation of the inhibitor effect of polifenol oxidaza enzyme in an avocado sauce (Persea americana) (2020)
This research is to rate the inhibition of Polyphenol Oxidase enzyme in a paste made of avocado (Persea Americana Mill) variety Hass through an onion peel (Allium Cepa) from two sorts of bulbs, white one and red one; exposed to two thermic treatments over 100°C and 115°C aiming to inhibit the effect of Polyphenol Oxidase which convert Phenols into Quinones causing the enzymatic browning. So that it implied to perform diversity of treatments, employing an inhibitor agent on different concentrations and periods of time in order to determine the ideal applications on determined times which required measuring the absorbance in four treatments, 1:0, 1.1, 1.2 and 2.1 respectively corresponding to the enzyme and the inhibitor agent, as a result of the enzymatic activity test a complete inhibition was reached for a concentration of 1:2 for the white bulb onion case in temperature of 100°C related to enzyme substratum; in red bulb onion case the inhibition varied for each treatment.